AN EMPIRICAL STUDY ON UNDERGRADUATE STUDENT ENGAGEMENT UNDER THE FLIPPED CLASSROOM MODEL - Yan Jin; Tan Choon Keong; Dg Norizah Kifle, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The flipped classroom offers many positive educational outcomes. Student engagement is an important indicator for assessing the quality of education in higher education and is a key factor in the success of curriculum reform. For this reason, assessing student engagement in the flipped classroom has always been a high priority. Purpose: The main purpose of this research is to use the Flipped Learning Student Engagement Scale to measure student engagement in the flipped classroom at a China university. The scale includes four engagement sub-scales, namely behavioral engagement, peer-relationship (emotional engagement- I), relationship with the faculty member (emotional engagement- II), and cognitive engagement, with 21 items in total. The scale has good stability, internal consistency, model fit, and constructs validity. Methods: Data were elicited via a survey approach and analysed quantitatively to support the investigation. The researcher selected a random sample of 507 university students from Long Dong University, Gansu Province, China. Results: The students reported that the overall engagement was generally good. Emotional engagement was significantly higher than behavioral and cognitive engagement. There were significant differences in students' levels of student engagement in terms of college, flipped learning experience, preferred course mode, type of preparation before the flipped classroom, and level of information technology. Conclusion: The research will provide a basis for evaluating and improving the current state of flipped learning engagement and optimizing student support services.